Exploitation of relations among the players of the mutton product cycle - Cehla, Béla; Kovács, Sándor; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2011)
The continuous weakening of Hungarian sheep sector and its low effectiveness in terms of value added have posed crucial problems in recent years.The focal problem has been partially caused by economic and market problems.Among these issues, mostly the poor mutton supply chain gives rise to difficulties; therefore the present study seeks to reveal the factors/input variables which predominantly influence the generation of value added. We have constructed a model for the mutton product cycle to represent the relations of phases but mutton trade is not included.The most significant aim of our investigation was to identify the volume of value added generated during processing in various phases of the product cycle and the change of which inputs affected this volume. The received findings suggested that in case of capital uniformity the output of processing was mostly influenced by sheep progeny on the bottom level of the mutton product cycle.